RELATIONSHIP MARKETING IN PROFFESIONAL SPORT - Iftime Dragoș Adrian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The scope of this study is to present the evolution of Barclays Premier League organization from the relationship marketing perspective and to analyze issues regarding the way in which the sportive organization implements the relationship marketing principles, which strategies is using and what are the main benefits, based on the examination of its history and its current practices. The relationship between sport organizations and the consumers of the sport product is a genuine bond; in fact the consumer is the sine qua non condition for the sport organizations to exist. Without constant reference to the final consumer, the professional sport finds itself in the situation of no means or reasons to outlast. Even more, all the transactions achieved on the sport market imply a certain level of expressing relationship marketing. This paper studies the impact of embracing the principles of relationship marketing in one of the most successful sportive organizations, Barclays Premier League, and the positive changes driven by this approach over the past decade. The research presents also the complex dynamic of creating and maintaining relations in professional sport as well as the implications of adopting a functional approach of the relationship marketing in this field. One important aspect refers to the added value this concept creates for the sportive organization. The result of this study consists of a set of recommended strategies and tactics to be introduced by a football club oriented towards achieving relationship marketing oriented goals that would help the organization to fully benefit from the implementation of this concept.